2017
DOI: 10.1007/s00259-017-3664-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the dopaminergic system and depressive symptoms in cervical dystonia

Abstract: PurposeCervical dystonia (CD) is associated with tremor/jerks (50%) and psychiatric complaints (17–70%). The dopaminergic system has been implicated in the pathophysiology of CD in animal and imaging studies. Dopamine may be related to the motor as well as non-motor symptoms of CD. CD is associated with reduced striatal dopamine D2/3 (D2/3) receptor and increased dopamine transporter (DAT) binding. There are differences in the dopamine system between CD patients with and without jerks/tremor and psychiatric sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 55 publications
(66 reference statements)
3
33
0
2
Order By: Relevance
“…However, when the density of DAT was assessed in other studies, the data indicated decreases in striatal DAT binding in depressed patients [24,94]. Likewise, in Parkinsonian patients, measures for anxiety and depression were associated with diminished left anterior putamen DAT binding [95], and striatal DAT binding was significantly lower in depressed versus non-depressed cervical dystonia patients [96]. The significant flaw in the results reported above is the absence of repeated cross-sectional studies that examine variations during phases of illness.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the density of DAT was assessed in other studies, the data indicated decreases in striatal DAT binding in depressed patients [24,94]. Likewise, in Parkinsonian patients, measures for anxiety and depression were associated with diminished left anterior putamen DAT binding [95], and striatal DAT binding was significantly lower in depressed versus non-depressed cervical dystonia patients [96]. The significant flaw in the results reported above is the absence of repeated cross-sectional studies that examine variations during phases of illness.…”
Section: Discussionmentioning
confidence: 99%
“…Included subjects also participated in another study recently published [ 5 ]. In short, we included patients with idiopathic CD with stable disease severity for at least 1 year on the Tsui scale, age between 35 and 80 years, and ongoing treatment with botulinum neurotoxin (BoNT) injections, which is the current standard treatment for focal dystonia.…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed normal striatal DAT binding but decreased D2/3 receptor binding in CD. We also showed a significant relationship between striatal DAT binding and jerks/tremor of the head, which is a common symptom in CD, and a significant and negative relationship between both striatal DAT and D2/3 receptor binding and depressive symptoms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using molecular imaging, abnormalities were found in dopaminergic signalling 7 8. We showed that lower striatal dopamine D 2/3 receptor and dopamine transporter (DAT) binding in CD is associated with depressive symptoms 8. We also found a clear trend towards lower serotonin transporter (SERT) binding in CD, particularly in patients with psychiatric symptoms.…”
Section: Introductionmentioning
confidence: 75%
“…After all videos of each subject were scored, physicians received the correct order for the videos and scored the CGI improvement for dystonia and jerks/tremor. Interobserver reliability was assessed in a subset of patients and was good (>80) for Tsui and TWSTRS and reasonable for UMRS (0.73) 8. The psychiatric interview was performed by trained investigators (EZ and YEMD) and consisted of the MINI International Neuropsychiatric Interview Plus (MINI-Plus), Montgomery-Åsberg Depression Rating Scale (MADRS) and the Y-BOCS Severity Scale.…”
Section: Methodsmentioning
confidence: 99%